2008
DOI: 10.4012/dmj.27.695
|View full text |Cite
|
Sign up to set email alerts
|

Bond strengths of two conventional glass-ionomer cements to irradiated and non-irradiated dentin

Abstract: This study evaluated the influence of irradiation on the dentin shear bond strength of two conventional glass ionomer cements (GICs). Thirty extracted molars were bisected in the mesio-distal direction. One-half of 20 teeth were irradiated with 60 Gy (5 days/week) for 6 weeks, and then GIC was placed on the irradiated dentin surface (Groups A1, B1). For the other halves of these tooth specimens, the GICs were first placed on their dentin surfaces and then the specimens irradiated (Groups A2, B2). The remaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 27 publications
0
13
1
4
Order By: Relevance
“…No entanto, raios X de alta energia têm sido preconizados (8,13) porque geram fótons com maior energia, liberando uma dose menor para o paciente. O protocolo de dose radioterápica utilizado em pacientes que possuem câncer na região de cabeça e pescoço é de, aproximadamente, 70,2 Gy, fracionados em doses diárias de 1,8 Gy (180 cGy) ao dia, totalizando 39 aplicações (17,20,32).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…No entanto, raios X de alta energia têm sido preconizados (8,13) porque geram fótons com maior energia, liberando uma dose menor para o paciente. O protocolo de dose radioterápica utilizado em pacientes que possuem câncer na região de cabeça e pescoço é de, aproximadamente, 70,2 Gy, fracionados em doses diárias de 1,8 Gy (180 cGy) ao dia, totalizando 39 aplicações (17,20,32).…”
Section: Discussionunclassified
“…Neste sentido, estudos têm avaliado o efeito da radioterapia sobre as propriedades mecânicas dos dentes (10)(11)(12)(13). Sua severidade e extensão sobre os tecidos dentais parecem ser dependentes do conteúdo mineral e orgânico das estruturas dentárias (10), que, após a irradiação, podem acomodar os radicais livres dentro da sua estrutura por longos períodos de tempo (14).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…9 Studies investigating the effects of different doses of radiotherapy on restorative material bond strength in permanent teeth produced inconclusive results, with some researchers suggesting that radiotherapy increases bond strength, while others conclude that there is either a decrease or no change. [5][6][7] There are currently no published studies evaluating similar effects of radiotherapy on the bonding strength of restorative materials to deciduous teeth. In this study, we investigated the effect of radiation on the µTBS between compomer resin and primary tooth enamel and dentin.…”
Section: Discussionmentioning
confidence: 99%
“…Another study that evaluated permanent teeth reported that the application of a single radiotherapy dose of 60 Gy caused a reduction in the bond strength between glass ionomer cement and dentin. 7 However, the effects of radiation on the bonding strengths between compomer resin restorative materials widely used in deciduous teeth and enamel and dentin hard tissue in deciduous teeth have not been studied. The aim of this study was to evaluate the effects of various doses of radiation therapy (10-60 Gy) on the µTBS of compomer resin restorative materials to the enamel and dentin of primary molars and also to compare the…”
Section: Introductionmentioning
confidence: 99%